2016
DOI: 10.1016/j.eats.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Hip Capsular Reconstruction Using Dermal Allograft

Abstract: Because hip arthroscopic procedures are increasing in number, complications related to the operation itself are starting to emerge. Whereas the capsule has been recognized as an important static stabilizer for the hip, it has not been until recently that surgeons have realized the importance of its preservation and restoration. Disruption of the capsule during arthroscopic procedures is a potential contributor to postoperative iatrogenic hip instability. In cases of a symptomatic deficient capsule, a capsular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…ITB allo- or autograft has been one of the most commonly used graft choices; however, some studies have reported the use of Achilles allograft or dermal allograft for capsular reconstructions. 6,25,28,46 Surgical techniques described in these studies include both arthroscopic and open approaches. 6,28,33,46 Neither approach has demonstrated superiority over the other, and regardless of the approach used, surgeons must balance the competing interests of preserving native tissues and ensuring adequate visualization.…”
Section: Discussionmentioning
confidence: 99%
“…ITB allo- or autograft has been one of the most commonly used graft choices; however, some studies have reported the use of Achilles allograft or dermal allograft for capsular reconstructions. 6,25,28,46 Surgical techniques described in these studies include both arthroscopic and open approaches. 6,28,33,46 Neither approach has demonstrated superiority over the other, and regardless of the approach used, surgeons must balance the competing interests of preserving native tissues and ensuring adequate visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Many capsuloligamentous reconstruction techniques have been previously described to address symptomatic instability in both native and non-native hip joints. [6][7][8][9] However, the technique in this paper is unique in that using a direct anterior approach to a native hip, the anatomic configuration of the iliofemoral ligament is replicated with an Achilles tendon bone block allograft to turn the original insufficient capsule into a now enhanced reconstructed iliofemoral ligament. Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative findings demonstrated continued capsular incompetency requiring capsular reconstruction with a dermal allograft (ArthroFlex; Arthrex, Napes, FL) augmentation as previously described. 33 This represents the only patient in this series who underwent capsular reconstruction.…”
Section: Complications and Reoperationsmentioning
confidence: 93%